2017
DOI: 10.1103/physrevb.95.064509
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent study of Abelian and non-Abelian order in a two-dimensional topological superconductor

Abstract: In the past few years, there has been a burst of theoretical and experimental activity in the field of topological insulators and topological superconductors. These materials represent new states of matter which are classified by an integer invariant and exhibit topologically protected conducting edge states which appear when the material is physically terminated.One of the consequences of topological superconductivity that makes this field significant is the possible existence of Majorana fermions as an eleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Introduction -Spin-orbit coupling (SOC) is ubiquitous in condensed matter systems and responsible for many remarkable phenomena [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In recent years, a surge of research interest in SOC was stimulated by the discovery that SOC plays a critical role in realizing various topological phases, ranging from non-interacting or weakly correlated topological insulators (TIs) and topological superconductors (TSCs) to strongly correlated topological phases [16][17][18][19].…”
mentioning
confidence: 99%
“…Introduction -Spin-orbit coupling (SOC) is ubiquitous in condensed matter systems and responsible for many remarkable phenomena [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In recent years, a surge of research interest in SOC was stimulated by the discovery that SOC plays a critical role in realizing various topological phases, ranging from non-interacting or weakly correlated topological insulators (TIs) and topological superconductors (TSCs) to strongly correlated topological phases [16][17][18][19].…”
mentioning
confidence: 99%
“…The current for spin-↓ is of equal magnitude and opposite direction, as required by time-reversal symmetry, such that the net current vanishes in this system. While the present study is focused on the spinbalanced system at half-filling, it has been suggested [11,36,37] that, with the introduction of a time-reversalsymmetry breaking Zeeman field and appropriate parameters, this system may host Majorana fermions. Meanfield calculations at half-filling indicate that the presence of a Zeeman field, even of considerable magnitude, is not sufficient to create spin-↑ and spin-↓ currents of different magnitude, and the system remains in a state with Chern number 0, ±2 [37].…”
mentioning
confidence: 99%
“…Hartree term can be incorporated into the effective local spin-dependent chemical potential µ → μiσ ≡ µ−U n iσ . As we shall see, impurities suppress the local order parameter χ i whose magnitude and sign depend on the coupling strength J [42,43].…”
Section: Model and Methodsmentioning
confidence: 79%